Variation in Experiencing Boredom during Self-Directed Learning in a Virtual World: The Case of One English Major - Kruk, Mariusz (Australian review of applied linguistics, 2021)
The paper presents the results of a study that aimed to investigate fluctuations in the levels of boredom in the virtual world of "Second Life" (SL) and factors accounting for such changes as reported by a single student of English philology. The participant took part in 15 sessions over the period of one summer semester. The learner was free to explore the virtual world in question, and she self-directed her own learning there. Using data collected by means of a set of research instruments (i.e., a background questionnaire, the Learning Style Survey, a session log, and a semi-structured interview), the study found that the student's experience of boredom was subject to some changes both in single sessions and from one visit to another. These fluctuations in boredom levels were affected by such factors as meeting the same interlocutors, scarcity of conversation topics, monotonous conversations, group chats or visits that the student perceived as not being beneficial for her language development.